Drivers of diversification in sharks and rays (Chondrichthyes: Elasmobranchii) - Gayford, Joel H.; Jambura, Patrick L. (Frontiers in Ecology and Evolution, 2025)
Elasmobranchs (sharks and rays) are a charismatic lineage of unquestionable ecological importance in past and present marine ecosystems. Represented by over 1200 species, elasmobranchs have undergone substantial shifts in taxonomic diversity since their origin. Quantifying these diversification trends and their underlying causes improves our understanding of macroevolutionary processes and the factors influencing community composition through deep time. Studies addressing drivers of diversification in Elasmobranchii have yielded conflicting results; some report clear relationships between specific traits and diversification events, whilst others fail to find support for such relationships. There is also some evidence to suggest that biotic interactions or environmental factors (global climatic change and tectonic events) have shaped elasmobranch diversification dynamics. In this review, we summarise the diversification dynamics of elasmobranchs over their evolutionary history, before considering the evidence for the three principal hypothesised drivers of diversification in this clade: trait evolution, biotic interactions, and environmental change. Finally, we discuss major limitations in the field, and how discordant methodologies and data sources hamper our current understanding of diversification in Elasmobranchii. Whilst future studies will undoubtedly be required to further unravel this complex relationship, no single factor can be considered the sole satisfactory explanation for observed deep time diversification trends in Elasmobranchii to the exclusion of the other.